FUTURE PERSPECTIVE AND WORK READINESS ON STUDENTS - Ridho, Ali; Siswanti, Ariska Dwi (Jurnal Psikologi, 2020)
This study aims to prove that the future perspectiveÂ  (FP) can be a good predictor of work readiness (WR) among college students. This study used the correlational method. A total of 90 eighth semester students (60 male, 30 female) from the Faculty of Science and Technology, Psychology, and Tarbiyah of the Universitas Islam Negeri Maulana Malik Ibrahim Malang became participants in this study. Participants' age ranged between 21-25 years (M = 23.7 years). This study used the adaptation of future perspective (FP) instruments from Husman and Shell (2008), which consists of 15 items, with Î± = 0.830, and the work-readiness adaptation instrument from Cabellero et al. (2011), which consists of 16 items, with Î± = 0.849. The researcher analyzed the data with bivariate linear regression. The study suggested a regression coefficient of B = 0.413 with t (89) = 5.314 p <0.01, r (88) = 0.493 p <0.01, and R2 = 0.243. These results indicate that FP has a strong relationship with WR, and FP can be a good predictor for WR. Therefore it can be concluded that FP supports the work readiness of students. This study suggests that students should be courageous in choosing meaningful activities to create a strong connection between the performed activities and the proposed career.Â